Does Corporate Governance Influence Voluntary Disclosure? Evidence from India - Saha, Rupjyoti; Kabra, Kailash Chandra (Indonesian Journal of Sustainability Accounting and Management, 2019)
The purpose of this study is to examine the influence of different corporate governance (CG) attributes on voluntary disclosures (VD) made by 100 companies listed on the Bombay Stock Exchange (BSE) in their annual reports. To this end, the paper uses appropriate panel data regression technique, whereby the results indicate that three CG attributes—board independence, board gender diversity, and its risk management committee—have significant influence on VD. In particular, board independence is found to have weak negative influence on VD while its gender diversity and risk management committee indicate strong positive influence on VD. The other CG attributes, specifically the board size, role duality, ownership concentration, audit committee independence, and nomination and remuneration committees, do not reveal any significant influence on VD. Overall, the finding suggests that one of the conventional attributes of CG, i.e. board independence, acts with VD as an alternate control mechanism to reduce agency costs and protect investor interests. Meanwhile, VD coexists with some of the latest CG attributes, including board gender diversity and its risk management committee, to monitor managers. The results of this paper should be relevant to regulators, practitioners, and other market participants in the Indian context, as well as other emerging markets with similar institutional settings.